2021
DOI: 10.36416/1806-3756/e20210229
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social distancing in response to COVID-19 on hospitalizations for laryngitis, tracheitis, otitis media, and mastoiditis in children aged 0 to 9 years in Brazil

Abstract: Objective: The objective of this study is to evaluate the impact of social distancing resulting from COVID-19 in hospitalizations for infections of the upper airways (URTI), such as acute laryngitis, tracheitis, and otitis media in children aged 0 to 9 years in Brazil, considering that they share the same forms of transmission. Methods: Data on hospitalizations for acute airway changes and their complications in children <9 years old were obtained from the Database of the Brazilian Department of Public Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
0
12
2
3
Order By: Relevance
“…Tal resultado se assemelhou aos de outras pesquisas, (14)(15)(16)(17)(18) que apontam para redução da procura pelos serviços de saúde por outras causas respiratórias que Fonte: Ministério da Saúde -Sistema de Informações Hospitalares do SUS (SIH/SUS). (3) não a COVID-19 em diversos países.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Tal resultado se assemelhou aos de outras pesquisas, (14)(15)(16)(17)(18) que apontam para redução da procura pelos serviços de saúde por outras causas respiratórias que Fonte: Ministério da Saúde -Sistema de Informações Hospitalares do SUS (SIH/SUS). (3) não a COVID-19 em diversos países.…”
Section: Discussionunclassified
“…No contexto brasileiro, o estudo de Silva et al, (14) direcionado à população pediátrica, concluiu ter havido uma importante queda nos atendimentos e internações de crianças durante a pandemia do novo coronavírus, coincidindo tais resultados com ao auferidos nesta revisão. Também os estudos ecológicos de Friedrich et al (15) e Jesus et al (16) identificaram diminuição significante das internações por pneumonia e por laringite, traqueíte, otite média e mastoidite entre as crianças, respectivamente. Resultados similares também foram evidenciados no cenário internacional.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Although presentation of COVID‐19 in hospital and outpatient settings continued to increase, presentation of other viral infections decreased 9 . Studies from various countries showed that the prevalence of OM decreased compared with pre‐pandemic prevalence 10–32 . Lockdowns, school closures, and social distancing caused decreases in the incidence of various viral infections including viral OM.…”
Section: Introductionmentioning
confidence: 99%
“…Population-based surveillance studies indicate lower transmission rates of viruses and bacteria associated with respiratory infection during the COVID-19-related lockdown 16 17. Based on both Danish and international data, it has now been shown that the introduction of the social distancing measures have reduced admission rates for respiratory tract infections for chronic obstructive pulmonary disease (COPD) and asthma exacerbations15 18 as well as paediatric admissions with both upper19 and lower respiratory tract infections 20 21. However, it has yet not been evaluated how the implementation of the social distancing measures affected persons with bronchiectasis.…”
Section: Introductionmentioning
confidence: 99%